The Criteria and Ethics of Educational Leadership in the Perspective of the Qur'an - Hasan, M Apip; Malik, Muhammad Hisyam (FKIP - Universitas Riau, 2025)
This article was written to address complex educational issues, such as declining learning quality, bullying, and acts of violence, which demand the presence of competent and ethical education managers. This study examines the criteria and ethics of an educational manager from the perspective of the Qur’an. It employs a qualitative approach based on a literature study using the maudhu’i (thematic interpretation) method. The primary data consists of relevant Qur’anic verses, supported by secondary sources from books and journals. The findings indicate that a Qur’anic-based manager must meet specific criteria, such as being knowledgeable (QS. 2:247), possessing integrity and competence (QS. 28:26), and demonstrating justice and managerial ability (QS. 16:90; QS. 39:62). In terms of ethics, a manager should be gentle (QS. 3:159), humble (QS. 17:37), honest (QS. 83:1-3), and serve as a good role model (QS. 33:21). These values support the role of the manager in creating a harmonious educational environment oriented toward collective success. This research emphasizes the importance of meritocracy in selecting educational managers and the need to apply Qur’anic values in educational management.